Soft dielectric actuator produced by multi‐material fused filament fabrication 3D printing. (6th March 2023) - Raguž, Ivan; Berer, Michael; Fleisch, Mathias; Holzer, Clemens; Brancart, Joost; Vanderborght, Bram; Schlögl, Sandra
Abstract: Dielectric elastomer actuators rely on Coulomb forces for their actuation. They are promising candidates when it comes to the manufacture of electrically driven soft and lightweight robotic devices, which can undergo large movement. However, their commercial availability and hence their technological relevance are still rather limited due to several reasons: in‐depth material knowhow in terms of electrical and mechanical behavior required; materials have to be available in thin sheets; complicated and error prone fabrication; limited design freedom. In order to change this, this paper presents a soft dielectric actuator fully produced by fused filament fabrication. Additive manufacturing with conventional fused filament fabrication machines offers the potential for the production of personalized dielectric actuators which are easily accessible and comparably cheap. The only requirement is a fused filament fabrication printer with multi‐material capability. Focusing on a mass customization of the 3D printed actuators, exclusively commercially available devices and filaments without any modifications are used. In particular, the 3D printed prototypes are characterized in terms of the maximum displacement depending on the electrode printing direction. As a showcase example, a soft dielectric gripper made of two 3D printed actuators is developed. Comparable with other dielectric elastomer actuators, a maximum displacement of 42% is reached.